Relation between three-dimensional and two-dimensional echocardiography and biochemical analysis in patients with ST-segment elevation myocardial infarction percutaneously treated - Vieira,Marcelo Luiz Campos (2010)
ABSTRACT Objective: The prognosis of patients with acute myocardial infarction depends on multiple features that can demonstrate myocardial injury degree (such as serum markers of cardiac necrosis), and also on adaptive mechanisms relative to the acute event. The aim of the study was to assess the relation between biochemical and echocardiographic findings from three-dimensional echocardiographic (3D Echo) analysis and echocardiographic two-dimensional (2D Echo) left ventricular ejection fraction in patients with ST-segment elevation acute myocardial infarction, submitted to primary percutaneous treatment. Methods: A prospective study with 2D Echo and 3D Echo of 23 patients (17 males, mean age of 57 ± 13 years) with ST-segment elevation acute myocardial infarction, primarily percutaneously treated (stent). Serum cardiac markers (creatine kinase MB, Troponin I and Myoglobin) and serum brain natriuretic peptide were compared to echocardiographic parameters (volumes, left ventricular ejection fraction and ventricular dyssynchrony index). The statistical analysis was performed using Pearson's correlation coefficient, 95% CI, p < 0.05, linear regression equation and Bland & Altman test. Results: Pearson's correlation coefficient (r)relative to 3D left ventricular ejection fraction: 1- brain natriuretic peptide: r: - 0.7427, p < 0.0001; 2- creatine kinase MB: r: - 0.660, p = 0.001. Left ventricular ejection fraction 2D (r) : 1- brain natriuretic peptide: r: - 0.5478, p = 0.001; 2- creatine kinase MB: r: - 0.4800, p < 0.0277. Other associations were not significant. Conclusions: In this series, it was observed better correlation in regard to serum creatine kinase MB, brain natriuretic peptide and 3D Echo left ventricular ejection fraction, when compared to 2D Echo left ventricular ejection fraction.